2019
DOI: 10.1111/cns.13086
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin mitigates cognitive impairment and protects neurons from microglia‐mediated neuroinflammation via suppressing NLRP3 inflammasomes and TLR4/NF‐κB signaling pathway

Abstract: Summary Aims Baicalin (BAI), a flavonoid compound isolated from the root of Scutellaria baicalensis Georgi, has been established to have potent anti‐inflammation and neuroprotective properties; however, its effects during Alzheimer's disease ( AD ) treatment have not been well studied. This study aimed to investigate the effects of BAI pretreatment on cognitive impairment and neuronal protection against m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
155
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(158 citation statements)
references
References 49 publications
3
155
0
Order By: Relevance
“…11,50 Activated glial cells release inflammatory factors that contribute to subsequent neuroinflammation. 51 In our study, we found that NR administration reduced neuroinflammation and suppressed the activation of microglia and astrocytes by decreasing the expression of TNF-α in the brain. The antiinflammatory effect of NR may be related to its ability to protect BBB integrity.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…11,50 Activated glial cells release inflammatory factors that contribute to subsequent neuroinflammation. 51 In our study, we found that NR administration reduced neuroinflammation and suppressed the activation of microglia and astrocytes by decreasing the expression of TNF-α in the brain. The antiinflammatory effect of NR may be related to its ability to protect BBB integrity.…”
Section: Discussionsupporting
confidence: 48%
“…BBB leakage leads to Ang ‐ entering the perivascular space, where Ang ‐ activates astrocytes and microglia by activating NFкB and signal transducer and activator of transcription protein 3 (STAT3) signaling . Activated glial cells release inflammatory factors that contribute to subsequent neuroinflammation . In our study, we found that NR administration reduced neuroinflammation and suppressed the activation of microglia and astrocytes by decreasing the expression of TNF‐α in the brain.…”
Section: Discussionmentioning
confidence: 53%
“…A wide range of therapeutic compounds (Table 3) have demonstrated their efficacy in animal models of AD-like pathologies, mainly by inhibiting TLR4 expression, suppressing microglial activation and pro-inflammatory cytokine levels, ameliorating learning and memory functions, inhibiting oxidative stress, and reducing apoptotic cell death and Aβ load (number and size of Aβ deposit) [120][121][122][123][124][125][126].…”
Section: Effects Of Tlr4 Blockade In Admentioning
confidence: 99%
“…Spicatoside A, which is one of the active compounds of Liriope platyphylla, also possess anti-inflammatory and memory repairment in animal models of dementia [146]. Scutellaria baicalensis Georgi and Lindera neesiana extract have potential anti-inflammation and neuroprotective properties, and can be used during AD progression [120,147,148]. Broccoli extract enriched in sulforaphane attenuates neuroinflammation, and because of its neuroprotective role, it can be used for combating neurodegenerative diseases, such as AD, PD, MS, and ischemia [149].…”
Section: Plant Extract or Phytochemical For Neurological Complicationsmentioning
confidence: 99%